A shortened whole brain radiation therapy protocol for meningoencephalitis of unknown origin in dogs - Herzig, Robert; Beckmann, Katrin; Körner, Maximilian; Steffen, Frank; Rohrer Bley, Carla (Frontiers in Veterinary Science, 2023)
Introduction A variety of treatment options have been described for canine meningoencephalitis of unknown origin (MUO). Few studies focused on radiation therapy as a second line immunomodulating treatment, implicating its effective use. However, a standard radiation therapy protocol is lacking, and further research will help to evaluate the effect of different dose regimens. Methods Ten dogs diagnosed with MUO based on MRI and CSF findings were prospectively enrolled. The dogs were treated with a shortened whole brain radiation therapy protocol (5 × 4 Gy) in combination with prednisolone. Neurologic changes were quantified using an established scoring scheme. Follow-up MRI and CSF examination was scheduled three months after radiation therapy. Overall survival and time to progression were calculated. Histopathology of the brain was performed in case of death. Results Seven dogs were diagnosed de novo and three had a history of relapsing MUO. Neurological status improved in all 10 dogs during radiation therapy, with 4/10 returning to normal shortly after radiation therapy. Three dogs died within the first three months after radiation therapy. At follow-up MRI lesions completely resolved in two dogs, partially resolved in five dogs, and progressed in one dog. After follow-up MRI, dogs were further treated with prednisolone monotherapy (two dogs) and additional immunosuppressant drugs (five dogs). Overall, four dogs showed disease progression, with a mean time to progression of 691 days (95%CI: 396–987) and mean overall survival for all dogs was 723 days (95%CI: 436–1011) (both medians not reached). Histopathology confirmed MUO in three dogs but was suggestive for oligodendroglioma in one dog. Radiation induced side effects were not seen. Conclusion Shortened whole-brain radiation therapy could be an additional treatment option for MUO in conjunction to prednisolone, specifically for cases that require rapid relief of symptoms and with relapsing history.